They didn't teach this in worm school! - Lia, Simone (Somerville, Massachusetts : Candlewick Press, 2018)
A worm and a chicken, who thinks he is a flamingo, set out on a madcap adventure in search of the chicken's "fellow flamingos" in Africa, and along the way, they forge an unlikely friendship.
Keywords: Worms -- Fiction; Chickens -- Fiction; Friendship -- Fiction; Worms -- Fiction; Chickens -- Fiction; Friendship -- Fiction; Humorous fiction; Humorous fiction